Revisiting governmentality in surf tourism governance: a diverse ecologies approach - Tara Ruttenberg; J. Peter Brosius (Frontiers in Sustainable Tourism)
Emergent discussions on governmentality in surf tourism scholarship apply a traditional Foucauldian perspective to analyze governance models in surf tourism destinations. Understanding governmentality as an “art of governance” creating and influencing human behavior, a handful of scholarly discussions have thus far engaged with Foucault's fourfold categories of neoliberal, sovereign, disciplinary, and (to a much lesser extent) truth governmentalities to interpret surf tourism governance in select locations. Importantly, this nascent thread of surf tourism research has yet to contend with Fletcher's novel framing of multiple governmentalities, which builds on Foucault's original categories and offers communal governmentality as a fifth category. Applying an anti-essentialist approach to the analysis of existing surf tourism governmentality literature, we identify diversity in surfscape governance approaches as an avenue for visibilizing communally self-determined futures in surfing destinations. We map multiple governmentalities as discussed in the literature across the five categories of “art of governance” philosophies and their associated governance principles, policies and subjectivities. The theoretical and empirical implications of a multiple governmentalities approach to surf tourism research can support and strengthen emancipatory community-based surfscape governance models challenging neoliberalism beyond otherwise essentializing frames.